Design and implementation of a pem fuel cell emulator for static and dynamic behavior (2011)
This paper presents the design, implementation, and experimental validation of a digitally-controlled emulator of proton exchange membrane (PEM) fuel cells for static and dynamic behavior. The emulator is a low cost, easy to use, and portable device designed to evaluate power systems and control strategies for fuel cell-based generation systems. For the implementation of this emulator, an appropriate mathematical model is chosen, parameterized, and experimentally validated. The resulting model is processed digitally by the emulator, which generates the appropriate electrical behavior to a load. The emulator power stage is implemented by using a two-inductor step-down DC/DC switching converter, which is controlled directly by the digital processing system. Later, the electrical scheme of the power stage and the block diagram of the system are presented, and the behavior of the emulator is illustrated with a simulation. Finally, the emulator is validated using experimental data.